Small Non-Coding RNAs at the Crossroads of Regulatory Pathways Controlling Somatic Embryogenesis in Seed Plants - Alves, Ana (2021)
Small non-coding RNAs (sncRNAs) are molecules with important regulatory functions during development and environmental responses across all groups of terrestrial plants. In seed plants, the development of a mature embryo from the zygote follows a synchronized cell division sequence, and growth and differentiation events regulated by highly regulated gene expression. However, given the distinct features of the initial stages of embryogenesis in gymnosperms and angiosperms, it is relevant to investigate to what extent such differences emerge from differential regulation mediated by sncRNAs. Within these, the microRNAs (miRNAs) are the best characterized class, and while many miRNAs are conserved and significantly represented across angiosperms and other seed plants during embryogenesis, some miRNA families are specific to some plant lineages. Being a model to study zygotic embryogenesis and a relevant biotechnological tool, we systematized the current knowledge on the presence and characterization of miRNAs in somatic embryogenesis (SE) of seed plants, pinpointing the miRNAs that have been reported to be associated with SE in angiosperm and gymnosperm species. We start by conducting an overview of sncRNA expression profiles in the embryonic tissues of seed plants. We then highlight the miRNAs described as being involved in the different stages of the SE process, from its induction to the full maturation of the somatic embryos, adding references to zygotic embryogenesis when relevant, as a contribution towards a better understanding of miRNA-mediated regulation of SE.